Synergistic Combination of Dual Clays in Multilayered Nanocomposites for Enhanced Flame Retardant Properties - Lee, Inyoung; Kim, Jinhong; Yun, Sehui; Jang, Junho; Cho, Se Youn; Cho, Jung Sang; Ryu, Ji Hyun; Choi, Dongwhi; Cho, Chungyeon (ACS Publications, 2024)
In an effort to reduce the flammability of synthetic polymeric materials such as cotton fabrics and polyurethane foam (PUF), hybrid nanocoatings are prepared by layer-by-layer assembly. Multilayered nanocomposites of a cationic polyelectrolyte, poly(diallyldimethylammonium chloride) (PDDA), are paired with two kinds of clay nanoplatelets, montmorillonite (MMT) and vermiculite (VMT). The physical properties such as thickness and mass and thermal behaviors in clay-based nanocoatings with and without incorporation of tris buffer are compared to assess the effectiveness of amine salts on flame retardant (FR) performances. A PDDA-tris/VMT-MMT system, in which tris buffer is introduced into the cationic PDDA aqueous solution, produces a thicker and heavier coating. Three different systems, including PDDA/MMT, PDDA/VMT-MMT, and PDDA-tris/VMT-MMT, result in conformal coating, retaining the weave structure of the fabrics after being exposed to a vertical and horizontal flame test, while the uncoated sample is completely burned out. The synergistic effects of dual clay-based hybrid nanocoatings are greatly improved by adding amine salts. Cone calorimetry reveals that the PDDA-tris/VMT-MMT-coated PUF eliminates a second peak heat release rate and significantly reduces other FR performances, compared to those obtained from the clay-based multilayer films with no amine salts added. Ten bilayers of PDDA-tris/VMT-MMT (approximate to 250 nm thick) maintain the shape of foam after exposure to a butane torch flame for 12 s. As for practical use of these nanocomposites in real fire disasters, spray-assisted PDDA-tris/VMT-MMT multilayers on woods exhibit high resistance over flammability. Improved fire resistance in PDDA-tris/VMT-MMT is believed to be due to the enhanced char yield through the addition of tris buffer that promotes the deposition of more clay particles while retaining a highly ordered deposition of a densely packed nanobrick wall structure. This work demonstrates the ability to impart significant fire resistance to synthetic polymer materials in a fully renewable nanocoating that uses environmentally benign chemistry.